Liberating the Gospels : reading the Bible with Jewish eyes : freeing Jesus from 2, 000 years of misunderstanding /: reading the Bible with Jewish eyes : freeing Jesus from 2, 000 years of misunderstanding. ([2009?]) - Spong, John Shelby
No abstract available